Body Mass Index Predicts 24-Hour Urinary Aldosterone Levels in Patients With Resistant Hypertension. Issue 4 (October 2016) - Dudenbostel, Tanja; Ghazi, Lama; Liu, Mingchun; Li, Peng; Oparil, Suzanne; Calhoun, David A.
Abstract : Prospective studies indicate that hyperaldosteronism is found in 20% of patients with resistant hypertension. A small number of observational studies in normotensive and hypertensive patients suggest a correlation between aldosterone levels and obesity while others could not confirm these findings. The correlation between aldosterone levels and body mass index (BMI) in patients with resistant hypertension has not been previously investigated. Our objective was to determine whether BMI is positively correlated with plasma aldosterone concentration, plasma renin activity, aldosterone:renin ratio, and 24-hour urinary aldosterone in black and white patients. We performed a cross-sectional analysis of a large diverse cohort (n=2170) with resistant hypertension. The relationship between plasma aldosterone concentration, plasma renin activity, aldosterone:renin ratio, 24-hour urinary aldosterone, and BMI was investigated for the entire cohort, by sex and race (65.3% white, 40.3% men). We demonstrate that plasma aldosterone concentration and aldosterone:renin ratio were significantly correlated to BMI ( P <0.0001) across the first 3 quartiles, but not from the 3rd to 4th quartile of BMI. Plasma renin activity was not correlated with BMI. Twenty-four–hour urinary aldosterone was positively correlated across all quartiles of BMI for the cohort ( P <0.0001) and when analyzed by sex (men P <0.0001; women P =0.0013) and race ( P <0.05), and stronger for men compared with women ( r =0.19, P <0.001 versus r =0.05, P =0.431, P =0.028) regardless of race. In both black and white patients, aldosterone levels were positively correlated to increasing BMI, with the correlation being more pronounced in black and white men. These findings suggest that obesity, particularly the abdominal obesity typical of men, contributes to excess aldosterone in patients with resistant hypertension. Abstract : Supplemental Digital Content is available in the text.